Pseudouridine in RNA: Enzymatic Synthesis Mechanisms and Functional Roles in Molecular Biology - Khan, Adil; Hu, Yu Dong; Khan, Salman; Aqeel, Sahibzada Muhammad; Khan, Imad; Hussain, Mudassar; AL-Ansi, Waleed; Xu, Guochao (International Journal of Environment, Agriculture and Biotechnology, 2023)
Pseudouridine, a common modified nucleotide, is prevalent in bacterial tRNA, rRNA, and snRNA. Initially identified in rRNA and tRNA, its presence extends to snRNA. Despite being the first identified and most prevalent RNA modification, its biosynthesis and diverse roles remain insufficiently understood. This extensively occurring modified nucleotide influences structural and functional attributes in various RNA categories. The isomerization process involves a carbon–carbon bond formation, and Pumilio family proteins (PUFs) are potential Ψ reader proteins. Pseudouridine, a ubiquitous constituent in structural RNAs, is notably absent in mRNA or viral RNAs. Its enzymatic isomerization occurs at the polynucleotide level, independently of cofactors. Compared to uridine, pseudouridine prefers the C3-endo conformation, enhancing stability in specific structural motifs. Evolutionarily conserved in major spliceosomal snRNAs, it plays a crucial role in spliceosome assembly and splicing. Pseudouridine (ψ), comprising 0.2–0.6% of uridines in mammalian mRNA, is enzymatically generated by pseudouridine synthases. Five pseudouridine synthase families orchestrate its site-specific isomerization. In eukaryotic and archaeal organisms, specific synthases rely on noncoding RNAs, like box H/ACA small nucleolar/scaRNPs. These modifications contribute to RNA structural stabilization and functional efficacy. In pre-mRNA and mRNA they guide splicing processes and protect against degradation, acting as a defense mechanism against viral infections. This review delves into the detection, structure, functions, and applications of pseudoridine in RNA. Methodologies like High-performance liquid chromatography, mass spectrometry, thin layer chromatography, enzyme-linked Immunosorbent assay, capillary electrophoresis, northern blotting, reverse transcript polymerase chain reaction and RNA bisulfite sequencing. establish a robust framework. Pseudouridine's roles in reinforcing RNA structures, modulating translation, and its potential in mRNA.